Diseño de un sistema de costos por órdenes de producción para el centro de acopio de la unión de organizaciónes indígenas jatarishun pertenecientes del Cantón Saquisilí - Mena Quimbita, Jessica Alexandra (2019)
All business are basically to satisfy the needs and customers desires, most of the entrepreneurs from which companies define their prices are performed according their competitors or empirically without knowing if they cover the costs, for which it is important to have a cost system that allows to control the entire productive system. for this reason, is necessary that the Collection Center of the Indigenous Organizations Union JATARISHUN dedicated to husking dry corn process, has a cost system for production orders for costs improvement and minimization involved in at shelling process. The present integrative project aims to improve the financial results through the identification of the elements those incurred during the productive process, allowing to know real costs. To carry out the project methods have been used that allowed to collect information in the organization and bibliographic collection, the technique used was the interview and the observation form that was applied to leaders and the people in charge of carrying out the process in order to obtain necessary and important information to develop the project. The main objective is oriented to the design of a cost system for production orders that allows to know the cost of the dry-kernel (shelling process) provided by the collection center, so this system will help with tools and to provide a quality service, also improving the performance of the person in charge with the leaders who will be able to establish prices for each process, as well as take decisions regarding the reduction of costs or expenses that arise in the processes. The proposed cost system is designed on spreadsheets that allow manipulate different modules referring to the resources that are part of the three cost elements, feeding enought information so that the real cost of the seven processes can be determined and the final accumulated cost of the provided service based on the need of each user.